Behaviour and load transfer mechanism of a novel I-beam to box-column connection. (April 2023) - Goudarzi, Alireza; Erfani, Saeed
Abstract: The recent studies on the connection of I-beam to box-column with a stub beam proposed by authors demonstrated the connection satisfactory performance. This paper discusses the load transfer mechanism of the connection. For this reason, reversed cyclic tests were conducted on the three configurations of the connection with different beam to column width ratios of 0.50, 0.67, and 0.75. The tested specimens revealed stable hysteresis curves. Furthermore, the experimental results show that the connection is fully restrained and qualified for use in special moment frames (SMF) according to AISC. The plastic hinge developed on the beam near to beam end-plate and met the requirements of extended end-plate connections. Also, the panel zone of connection remained elastic throughout the tests. The study of load transfer mechanism revealed that by transferring the major portion of load to the column webs, the normal stress in the column flange is reduced, leading to the elimination of the need for continuity plates. Moreover, the finite element models of tested specimens were simulated. After the verification of numerical models against experimental results, they were extended to examine the effects of stub beam length and beam to column width ratio on the load transfer mechanism. According to the numerical results, the load transfer mechanism at the stub beam to column joint location was not sensitive to the changes in stub beam length and beam to column width ratio. Graphical abstract: Unlabelled Image Highlights: Cyclic tests were conducted on all the configurations of the proposed connection. The connection configurations satisfy AISC seismic provision requirements for SMF. The load transfer mechanism was evaluated and components contribution was determined. Load is mainly transferred to column webs eliminating the need for continuity plates. Stub beam length and width ratio changes do not disrupt the load transfer mechanism.